Effect of intraoral digital sensor colour variation and connection cable position on discomfort level in periapical (PA) radiography technique / Shahrani Janudin, Harith Fadhilah Halim, Zanariah Mohd - Janudin, Shahrani; Halim, Harith Fadhilah; Zanariah, Mohd (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Peripical (PA) technique is one of the intraoral radiography techniques that requires the image receptor such as film and sensor to be inserted into the oral cavity. This may lead to discomfort especially with the use of current digital sensor. Current design by most of the vendors highlighted the need of ergonomic shape and optimum thickness to minimize the discomfort. This study evaluated the effect of sensor's colours and cable position on discomfort feeling during PA. An experimental approach using pre and post intervention technique to evaluate the respondents' feedback with the use of the sensors was conducted. A total number of 47 respondents were selected from Faculty of Health Sciences, Universiti Teknologi MARA (UiTM) via systematic random sampling. The respondents experienced different design of digital intraoral sensor during the simulation of PA dental radiography procedure for posterior teeth. A Numeric Rating Scale (NRS) scoring were adopted to assess and compare any discomfort experienced by the respondents. The descriptive analysis showed that median NRS score value was higher for dark blue colour sensor (median = 8) as compared to the black sensor (median=7). The Wilcoxon matched paired sign rank test showed that there was a significant difference in terms of the discomfort level experienced by the respondents (p < 0.001). For the cable connection design, the median score value of corner position is greater recorded as 7, than the cable connection position at the centre which the median is 6. Cable connection position at the centre was less discomfort as compared to cable connection located at the corner of the sensor. As conclusion, the colour and cable connection location could affect the discomfort level during PA radiography technique.